2014
DOI: 10.1186/1477-7819-12-164
|View full text |Cite
|
Sign up to set email alerts
|

Secondary bile acids: an underrecognized cause of colon cancer

Abstract: Bile acids were first proposed as carcinogens in 1939. Since then, accumulated evidence has linked exposure of cells of the gastrointestinal tract to repeated high physiologic levels of bile acids as an important risk factor for gastrointestinal cancers. High exposure to bile acids may occur in a number of settings, but most importantly, is prevalent among individuals who have a high dietary fat intake.A rapid effect on cells of high bile acid exposure is the generation of reactive oxygen species and reactive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
244
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 311 publications
(258 citation statements)
references
References 53 publications
3
244
1
1
Order By: Relevance
“…A report on concentration of secondary fecal bile including 15 healthy individuals concluded that wheat and rye fiber (rich in cellulose) lead to low concentration in the fecal bile [46]. High bile acid concentration can also lead to colon cancer, it was considered in "carcinogens" in 1939, and the most dominant cause was fat intake, since it was prevalent among individuals who have a high dietary fat intake [47]. Evidence has been showed to prove the mechanism of secondary bile acids effect leading to colon cancer [47].…”
Section: Insoluble Fiber; Cellulose Role In Cancer Development Mechamentioning
confidence: 99%
See 1 more Smart Citation
“…A report on concentration of secondary fecal bile including 15 healthy individuals concluded that wheat and rye fiber (rich in cellulose) lead to low concentration in the fecal bile [46]. High bile acid concentration can also lead to colon cancer, it was considered in "carcinogens" in 1939, and the most dominant cause was fat intake, since it was prevalent among individuals who have a high dietary fat intake [47]. Evidence has been showed to prove the mechanism of secondary bile acids effect leading to colon cancer [47].…”
Section: Insoluble Fiber; Cellulose Role In Cancer Development Mechamentioning
confidence: 99%
“…High bile acid concentration can also lead to colon cancer, it was considered in "carcinogens" in 1939, and the most dominant cause was fat intake, since it was prevalent among individuals who have a high dietary fat intake [47]. Evidence has been showed to prove the mechanism of secondary bile acids effect leading to colon cancer [47]. Their amphipathic nature enables them to get involved in emulsification and digestion of dietary fats; yet, levels above those that are physiologic are potentially membrane damaging [48].…”
Section: Insoluble Fiber; Cellulose Role In Cancer Development Mechamentioning
confidence: 99%
“…For example, the dysregulation of bile acids has close relationship with gastrointestinal cancer 8 . Secondary bile acids have been considered to be a cause of colon cancer 9 . The experiments performed by Liu et al showed that conjugated bile acids promoted cholangiocarcinoma cell invasive growth through the activation of sphingosine 1-phosphate receptor 2 10 .…”
Section: Discussionmentioning
confidence: 99%
“…When Nehra and colleagues profiled esophageal aspirates in the patients suffering from erosive esophagitis and Barrett's esophagus and compared with that of healthy individuals, they found significantly increased proportion of secondary bile acids, deoxycholic acid and taurodeoxycholic acids to be present in patients with erosive esophagitis and BE (505). Bile acids (especially secondary bile acids) are known for their causative roles for many gastrointestinal cancers (506,507). At physiological levels repeated and prolonged exposure of bile acids in esophageal tissue, which is not meant to deal with gastric/bile acid, can cause oxidative/nitrosative stress, DNA damage leading to generation of genomic instability, apoptosis, and ultimately cancer (508,509).…”
Section: Bile Acids Microbiome Diet and Glycan: Is There A Link?mentioning
confidence: 99%
“…Bile acids are physiological detergents and enable absorption of lipids, cholesterol, and fatsoluble vitamins from the gastrointestinal tract (507). Cholic acid and chenodeoxycholic acid are primary bile acids which are derived from cholesterol by a sequence of enzymatic reactions that involve 17 different enzymes and occur mainly in the liver (510).…”
Section: Bile Acids Microbiome Diet and Glycan: Is There A Link?mentioning
confidence: 99%